GENDER INEQUALITY IN THE HOSPITALITY SECTOR OF CENTRAL ASIA - Madina Kayumova, (Ta'lim innovatsiyasi va integratsiyasi, 2025)
Abstract: hile tourism is on the rise in countries like Uzbekistan,  Kazakhstan, Kyrgyzstan,  and  Tajikistan,  women  still  encounter  significant  obstacles  in  the workplace. They often find themselves in low-paying, customer service roles, earn less than their male counterparts, and have limited opportunities to advance into leadership positions. This paper explores the issue of gender inequality in the hospitality industry across Central Asia. The paper reviews various studies and reports that highlight how cultural  norms,  social  expectations,  and  workplace  practices  contribute  to  these challenges. It also points out that even when governments implement laws and policies aimed at supporting women, these measures often fall short in practice. By synthesizing information from multiple studies, the paper sheds  light on the persistent nature of gender inequality and suggests what changes are necessary to foster better and fairer opportunities for women in the hospitality sector.